Cournot competition in the joint products market under demand uncertainty. (21st January 2021) - Okura, Mahito
Abstract : The purpose of this study is to analyze the market in Cournot competition under demand uncertainty when two firms compete with two joint products which are indivisible multiple goods, such as petroleum products. We investigate the situations in which no, either, or both firms have either no demand information or have demand information in one or both markets and examine how the differences in information structures affect the equilibrium expected profit of each firm.